Effect of Staining and External Bleaching on the Color Stability and Surface Roughness of Universal-Shade Resin-Based Composite - AlHabdan A; Alsuhaibani A; Alomran L; Almutib L (Clinical, Cosmetic and Investigational Dentistry)
AlHanouf AlHabdan,1 Amal Alsuhaibani,2 Lama Alomran,2 Lulwah Almutib2 1Department of Restorative Dental Sciences, King Saud University, Riyadh, Saudi Arabia; 2College of Dentistry, King Saud University, Riyadh, Saudi ArabiaCorrespondence: AlHanouf AlHabdan, Department of Restorative Dental Sciences, King Saud University, Riyadh, Saudi Arabia, Email alhabdan@ksu.edu.saAim: This study evaluated the color stability and surface roughness of two universal-shade compared to two nanohybrid composites after staining and external bleaching with 40% hydrogen peroxide.Methods: Two universal shade resin-based composites and two nanohybrid composites were tested. Twenty disc-shaped specimens from each material were fabricated and divided into two subgroups: one group was stained and bleached (staining group) and the other received bleaching treatment only (control group). The staining group was stained with coffee solution for 24 h. Subsequently, each sample of all four materials was bleached using an in-office bleaching gel using 40% hydrogen peroxide. Color measurements were performed using a spectrophotometer to obtain the International Commission on Illumination parameters, L*; a*; and b* for each of the following periods: baseline, after bleaching, and two weeks after bleaching for the control group. The staining group was examined at baseline, after staining, after bleaching, and two weeks after bleaching. Surface roughness (Ra) of all the materials after each treatment step were also recorded. The data was statistically analyzed using SPSS 26.0 statistical software. Changes were considered statistically significant at P = 0.05.Results: Descriptive statistics (means and standard deviations) were used to describe color measurements and surface-roughness values. Two-analysis of variance and one-way analysis of variance were used to compare the mean values of surface roughness, L*a*b*and ΔE00 values. Statistically significant differences and clinically acceptable ΔE00 were observed between all materials during the different stages in color measurements, whereas the surface roughness was significantly different for each study material and treatment mode.Conclusion: Staining with coffee solution and external bleaching produced acceptable color changes for all materials tested. Staining and bleaching increased the surface roughness values of the tested resin-based composites.Keywords: composite, surface roughness, bleaching, teeth, spectrophotometer, profilometer